PRAKTIK PENGALAMAN LAPANGAN BERBASIS LESSON STUDY (LS) UNTUK MENINGKATKAN KETERAMPILAN KOMUNIKASI DAN KOLABORASI MAHASISWA - Dipalaya, Tismi (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2020)
In the Natural Sciences Curriculum Development Program at UM Biology Education, not all students are active and skilled in expressing opinions so that during the class discussion process, not all students are able to express their ideas to solve the problems given by the lecturers. Through Lesson Study based learning, it is hoped that communication and collaboration skills of students will increase. The research approach used is a qualitative approach and the type of research is classified as action research based on Lesson Study. The results showed that LS-based learning can improve student communication and collaboration skills.